ANALISIS INVESTASI DAN PENDAPATAN DAERAH SUMATERA UTARA - Siregar, Enni Sari; Wardi, Yunia; Aimon, Hasdi (Jurnal Kajian Ekonomi, 2014)
This article focused on analyze (1) Effect of the income, interest rates, government expenditure, and inflation to investment in North Sumatera. (2) The influence of investment, government expenditure, inflation, money supply, and tax on the income in North Sumatera. Data used time series of 1982 - 2012. This article use analyzer model equation of simultaneous with method of Two Stage Least Squared (TSLS). The result of research concludes that (1) the income have a significant and positive impact on the investment, interest rates have significant and negatively impact on the investment, government expenditure significantly and positive on the investment, while inflation is not significant and negative effect on the investment in North Sumatera. If income increases, the investment will also increase. If interest rates increases, the investment will decreases, and If government expenditure increases, the investment will increases. (2) the investment have a significant and positive impact on the income, government expenditure is not significant and positive on the income, the money supply have significant and positive impact on the income, and tax have significant and negatively impact on the income in North Sumatera. If investment increases, the income will also increase,Â  if the money supply increase, the income will increase, and then if the tax increase, the income will decreases. Keywords :interest rates, goverment expenditure, inflation, the money supply, tax, income and investment